Implementation of Accounts Receivable Control Against the Risk of Doubtful Accounts at PT. Radhar Delta Bersaudara Sidoarjo Branch - Amin Sadiqin (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2021)
This study aims to determine the implementation of internal control of accounts receivable against the risk of bad debts. The author finds that this research is important to become new knowledge about internal control of accounts receivable in a company. This research uses a qualitative approach. This research was conducted at the PT. Radhar Delta Bersaudara, Sidoarjo branch. The data used in this study are primary data and secondary data. The data analysis used descriptive qualitative. Based on the results of the analysis, it can be concluded that the internal control of accounts receivable for the risk of bad debts at PT. Radhar Delta Bersaudara has done very well as evidenced by a decrease in the number of uncollectible accounts from 2015-2019.